Image-based simulation of brain arteriovenous malformation hemodynamics - Orlowski, P; Noble, J; Ventikos, N; Byrne, J; Summers, P; IEEE (2008)
A novel image-based patient-specific simulation method has been developed incorporating computational fluid dynamics (CFD) and porous media principles which presents, for the first time, patient-specific blood flow through an arteriovenous malformation of the brain (BAVM). The new approach constructs an image-based geometric model of a malformation where the BAVM nidus is modelled as a porous medium. The method has been applied to a brain BAVM case with two feeding and four draining vessels. A qualitative comparison of the simulation results with blood flow imaging data shows the promise of the approach and suggests that the method may find application in planning for BAVM treatment. ©2008 IEEE.